PERANCANGAN IKLAN LUAR RUANG DALAM MEDIA TRANSIT ADVERTISING TEXAS JUICE DI KOTA BUKITTINGGI - OKI SIKUMBANG, Dra. Zubaidah, M.Sn., Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Texas Juice was founded in 2006 by Lisa Vitria derived from Maninjau. Juice Texas name stems from the idea when invited by BTV, the local television broadcast in the program "Women's Work". Texas Juice is a small industry that serves a wide variety of food and drink menu, but more specialized for serving drinks juice made from fresh fruits with different flavors and variants. Besides the uniqueness presented by Texas in the manufacture of juice Juice is the owner of combining 2 to 3 flavors of juice in the presentation. That is the main attraction forconsumers.This thesis aims to generate an advertising medium on Texas Juice. The design method used by the authors is the beginning of a method of collecting data through observation, interviews, and documentation. Then proceed with the data analysis method using data analysis Strengths, Weakness, Opportunities, andThreat (SWOT), further concluded perform data analysis and creative approach (the main media and supporters). In the design of transit media, the writer displays a message or verbal and visual information for consumers.With he designed transit media is expected to increase and become a consumer or public appeal. In addition, is expected to attract the attention of buyers or the public at large so as to enhance the efforts of existence culinary field named Texas Juice in Bukittinggi.Keywords: Media Transit, Texas Juice, Design.